MANIFESTASI NILAI TRADISIONAL RIASAN PENGANTIN KONTEMPORER DALAM MATA PELAJARAN TATA RIAS DAN KECANTIKAN DI SMK - Zesi Zarmasi Sarwendah (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
The objective of the study is to know 1)SMK response on the development of contemporarybridal makeup subjects, 2) The development ofbridal makeup subjects, 3) Manifestation oftraditional value of contemporary bridal makeup inbeauty and cosmetology subjects in vocationalschool. This research uses the qualitative approach.Sources of research data based on information frombeauty and cosmetology leather teachers, heads ofcosmetology and beauty majors, three studentsthrough interviews, observation, anddocumentation. Qualitative data analysis techniquewith an interactive model. The results showed: 1)the SMK has not responded about the bridal makeup2) The development effort was done, the studentslooking for the reference source of cosmetology anddiscussed with the teacher, following the makeupevent (Carnival, Performance, LKS), 3)Manifestation of traditional makeup valuecontemporary brides the main influence of thedevelopment of the era and the role of informationmedia